Strategi Komunikasi Pemasaran Digital Dalam Meningkatkan Minat Pariwisata Pulau Pari (Mix Method: Exploratory Sequential Design) - Muhamad Alimudin; Desak Made Dharmawati (Jurnal EMT KITA, 2022)
The tourism sector is confirmed to be a significant economic growth sub-sector in Indonesia, especially on Pari Island which has tourism potential that can contribute to the country's foreign exchange. However, complex problems with digital marketing communication strategies and Covid-19 have occurred in recent years. This study aims to explore digital marketing communication strategies for increasing tourist visits. This type of research is Mix Method Exploratory Sequential Design used with 2 phases. Phase 1 is the qualitative technique, purposive sampling, data collection is by observation and semi-interviews and the analysis is Interactive Model Analysis and phase 2 is a quantitative technique, saturated sampling (N=20), and the analysis is Simple Linear Regression. The results show that in phase 1 (qualitative approach), the travel manager of the Pari Island tourist attraction applies a digital marketing communication strategy to increase tourist visits, namely Advertising, Sales promotion, Direct Marketing, Personal selling, and Public Relations. Phase 2 (quantitative approach) confirms that the digital marketing communication strategy has a significant effect on tourism interest. The implications of the research suggest that tourism travel managers and tourism offices can implement good digital marketing communication strategies in order to increase tourist visits to Pari Island after the Covid-19 pandemic.